FAMILY ANAMNESIS OF CHILDREN WITH MUTATION OF THE INHERITED HEMOCHROMATOSIS - S.I. Polyakova (Педиатрическая фармакология)
The inherited burdened is studied on diseases, associated with an overload iron in 41 children with frequent mutations of the inherited hemochromatosis (IG) of a 1 type (C282y, H63d, S65c). Control group was made by 27 children with undiscovered frequent mutations of NG. Frequencies of iron-associated diseases are compared for 560 members of families which have children with mutations of IG and 390 members of families which have children without IG mutations. Some features of medical-genealogical anamnesis, which can be conditioned of siderosis, are exposed, and indirectly specify in the presence of mutations in the gene of HFE. So, the high frequency of oncologic diseases, diabetes mellitus, hepatocirrhosis and deaths of relatives under the age of 50 years are the foundation for research of exchange of iron and holding of molecular-genetic research of the inherited hemochromatosis. Key words: inherited hemochromatosis, heredity, children. (Pediatric Pharmacology. – 2010; 7(3):52-56)